1998
DOI: 10.1046/j.1365-2133.1998.02548.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the calcium-dependent protease, calpain, during keratinocyte differentiation

Abstract: Calpain is a ubiquitous neutral calcium-activated thiol protease that is implicated in various cellular functions including exocytosis, cell fusion, apoptosis and proliferation. The calpain system is composed of the enzymes mu-calpain and m-calpain and their endogenous inhibitor, calpastatin. We employed the spontaneously immortalized human HaCaT keratinocytes, which retain their ability to differentiate in vitro and in vivo, to study the modulation of the calpain system during keratinocyte differentiation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
7
29
0
Order By: Relevance
“…5). Results obtained for LC-TP and HC-TP were similar to those observed previously: (1) LC cells were mainly in G0/G1, due in part to confluence, which induced differentiation [12,13,15]; (2) whereas HC cells accumulated in S/G2-M [14]. The cell cycle profile of HC-F2 (Fig.…”
Section: Analysis Of Dna Content By Flow Cytometrysupporting
confidence: 91%
See 1 more Smart Citation
“…5). Results obtained for LC-TP and HC-TP were similar to those observed previously: (1) LC cells were mainly in G0/G1, due in part to confluence, which induced differentiation [12,13,15]; (2) whereas HC cells accumulated in S/G2-M [14]. The cell cycle profile of HC-F2 (Fig.…”
Section: Analysis Of Dna Content By Flow Cytometrysupporting
confidence: 91%
“…Like NHKs, HaCaT differentiation is induced either with confluence, when cells are cultured in a calcium free medium [12][13][14][15] or with Ca 2+ concentrations superior to 1 mM [62,63]. In both cell types, Ca 2+ -induced differentiation is observed by an increased expression of differentiation markers, such as K1, K10 and involucrin [5][6][7][8][9][10].…”
Section: Analysis Of Dna Content By Flow Cytometrymentioning
confidence: 99%
“…The protease has been detected in the upper part of the epidermis (43), and its expression has been shown to be up-regulated during keratinocyte differentiation in vitro (44). In our studies, in vitro cleavage assays revealed that calpain 1 was able to directly process a fragment of FLG2 consisting of B-type repeats B7-B10 into multiple peptides detected by both immunoblotting and mass spectrometry.…”
Section: Discussionmentioning
confidence: 78%
“…59 In these tissues, Myc-nick may be involved in mediating at least some of the functions attributed to the myc gene in terminal differentiation and tissue maintenance. Furthermore, during keratinocyte differentiation calpains are activated 28 and there is an increase in tubulin acetylation, 62 suggesting a correlation with Myc-nick production and function. In a keratinocyte model for the autoimmune disease Pemphigus vulgaris, a smaller form of Myc, with a size corresponding to that of Myc-nick, was detected predominantly in the cytoplasm.…”
Section: Moonlighting Mediated By Calpain Cleavagementioning
confidence: 99%
“…While hyperactivation of calpains is associated with increased tumorigenesis, 27 regulated increases in calpain activity are essential for terminal differentiation of multiple cell types. Calpains are upregulated and activated during differentiation of keratinocytes, 28 hematopoietic 29 and muscle cells, 30,31 among others. Importantly, mutations in the muscle-specific calpain 3, which impair its proteolytic activity, are the sole cause of limb girdle muscular dystrophy 2A (LGMD2A).…”
Section: Post-translational Control Of Myc Function During Differentimentioning
confidence: 99%